Anthrax of the lower eyelid - Koçer, Ugur (Pulsus Group Inc, 2003)
Because cutaneous anthrax, caused by Bacillus anthracis, is rare in developed countries, sporadic cases of anthrax may easily be overlooked because the diagnosis is often difficult to make. Lower eyelid involvement of anthrax is rare in clinical practice. A 40-year-old woman with a history of contact with animals was evaluated and treated for a left lower eyelid lesion with a black eschar on it. A diagnosis of cutaneous anthrax had been made and intravenous penicillin had been given by the department of infectious diseases before plastic surgery consultation. Any kind of surgical intervention was delayed for three months. The lesion healed secondarily and the resulting scar did not result in ectropion of the lower eyelid. Delaying surgery is preferred because it is a safer approach when dealing with anthrax involving the lower eyelid, and secondary healing does not always result in deformity compromising function.